Rice plants treated with biochar derived from Spirulina (Arthrospira platensis) optimize resource allocation towards seed production - Minello, Luana Vanessa Peretti; Kuntzler, Suelen Goettems; Lamb, Thainá Inês; Neves, Cleo de Oliveira; Berghahn, Emílio; da Paschoa, Roberta Pena; Silveira, Vanildo; de Lima, Jeferson Camargo; Aguzzoli, Cesar; Sperotto, Raul Antonio (Frontiers in Plant Science, 2024)
The use of biofertilizers is becoming an economical and environmentally friendly alternative to promote sustainable agriculture. Biochar from microalgae/cyanobacteria can be applied to enhance the productivity of food crops through soil improvement, slow nutrient absorption and release, increased water uptake, and long-term mitigation of greenhouse gas sequestration. Therefore, the aim of this study was to evaluate the stimulatory effects of biochar produced from Spirulina (Arthrospira platensis) biomass on the development and seed production of rice plants.Biochar was produced by slow pyrolysis at 300°C, and characterization was performed through microscopy, chemical, and structural composition analyses. Molecular and physiological analyses were performed in rice plants submitted to different biochar concentrations (0.02, 0.1, and 0.5 mg mL -1 ) to assess growth and productivity parameters. Morphological and physicochemical characterization revealed a heterogeneous morphology and the presence of several minerals (Na, K, P, Mg, Ca, S, Fe, and Si) in the biochar composition. Chemical modification of compounds post-pyrolysis and a highly porous structure with micropores were observed. Rice plants submitted to 0.5 mg mL -1 of biochar presented a decrease in root length, followed by an increase in root dry weight. The same concentration influenced seed production, with an increase of 44% in the number of seeds per plant, 17% in the percentage of full seeds per plant, 12% in the weight of 1,000 full seeds, 53% in the seed weight per plant, and 12% in grain area. Differential proteomic analyses in shoots and roots of rice plants submitted to 0.5 mg mL -1 of biochar for 20 days revealed a fine-tuning of resource allocation towards seed production. These results suggest that biochar derived from Arthrospira platensis biomass can stimulate rice seed production.-Spirulina-derived biochar presents composition and structure suitable for use in agricultural systems.-Exposure of rice plants to biochar for 20 days leads to proteomic changes in shoots and roots.-Rice plants treated with biochar optimize resource allocation towards seed production.